A introdução da televisão na esfera familiar paulistana nos anos 50: as transformações nos vínculos comunicativos familiares - Mello, Fabiana Grieco Cabral de (2007)
This research analyzes the way television was introduced in the family environment, mainly in that one representing the patriarchal model of the 50´s in the city of São Paulo, Brazil, as well as the consequences of this process in the established communicative bonds in this sphere. Therefore, the historical period along with the family scenario were contextualized, considering their main characteristics from a communication viewpoint. Moreover, a definition of the ways and means of achieving the dissemination of this new media was investigated: the main topics inserted in this process, programs that stood out in the history of television, the making of stars and the beginning of the scheduling of subjects, known as agenda-setting . In order to achieve such goal, the methodology used was that of historical research, bibliographical research and in-depth interviews. The historical research was done through study of the advertising section of the following newspapers: "O Estado de São Paulo", "A Folha da Manhã" and Folha de São Paulo . Through bibliographical research, the question of the introduction of the TV in the familiar sphere and its consequences was analyzed according to the works of many communication experts, such as Edgar Morin, Boris Cyrulnik and Harry Pross, with special emphasis on this last author. The ideas of these specialists have allowed discussion as to whether the introduction of television in the scope of familiar communication respected the chances and the capacity of social dialogue among family elements, or if it invested in the development of the multiplicity that leads to isolation and the loss of social communication. The result of the research evidenced that the television intervened in the interpersonal relationships dynamics and was really able to transform the family communicative bonds. It is worth, thus, to point out the contribution of this paper to the studies of the Communication and Semiotics while casting an eye over our own history and broadening the horizons of knowledge that can improve the performance of our communicative abilities, in the midst of the family or in the most diverse social spheres